Application of metaheuristic in inventory routing problems / Nur Arina Bazilah binti Aziz - Aziz, Nur Arina Bazilah (2013)
The coordination of the inventory management and transportation is often known as the Inventory Routing Problems (IRP). The problem addressed in this study is outbound and inbound distribution network consisting of an assembly plant and many geographically dispersed suppliers/customers where the supplier/customers supplies/receives distinct product to/from the assembly plant. It is based on a finite horizon, multi-periods, multi-suppliers and multi-products where a fleet of capacitated homogeneous vehicles, housed at a depot, transport parts from/to suppliers/customers to meet the demand specified by the assembly plant in each periods. We propose a hybrid genetic algorithm based on allocation first, route second method to determine an optimal inventory and transportation policy that minimizes the total costs. We introduce two new representations. The first is based on a